مدارس الإقراء في اليمن في عصر الدولة الرسولية 626هــ-858هــ / 1229م-1454م - الحداد، مني عبدالله محمد (جامعة القرآن الكريم والعلوم الإسلامية, 2021)
تناولت الدراسة التعريف بالدولة الرسولية، من خلال لمحة تاريخية ولمحة علمية عنها، وهدفت الدراسة إلى بيان أهم مدارس الإقراء التي أسسها وبناها ملوك وأمراء بني رسول في اليمن لتدريس القراءات. وكانت منهجية الدراسة المنهج الوصفي القائم على جمع المعلومات من المراجع والمصادر المختلفة، وخلصت الدراسة إلى عدد من النتائج أهمها: أن الدولة الرسولية كانت من أكبر الدول السنية التي استطاعت بسط نفوذها على أغلب أجزاء اليمن، وكان لهم دورا في الحياة العلمية في اليمن، وأولو دور العلم جل عنايتهم، فشيدوا المدارس، وألحقوا بها خزائن الكتب، وأنشأوا مدارس متخصصة في تدريس علوم بعينها كالقراءات والحديث والفقه. إضافة إلى المدارس المشتركة، ولم يقتصر إنشاء المدارس على سلاطين الدولة، بل أسهم فيه الأمراء والفقهاء، وبعض الوزراء ونساء البيت الرسولي، كما أن المدارس المتخصصة في علم القراءات كان لها دورا في إخراج قدر كبير من المقرئين في ذلك العصر. كما توصلت الدراسة إلى عدد من التوصيات أهمها: توسيع دائرة البحوث والندوات والمؤتمرات عن مدارس الإقراء في اليمن، وطباعة الكتب اليمنية في علم القراءات لتعريف الخلف بما تركه لهم السلف ليسهم في تحفيزهم فيحذو حذوهم، وإثراء المكاتب العربية بجهود اليمنيين في تشييد المدارس الإسلامية ومدارس الإقراء، من خلال طباعة الكتب والأبحاث التي تناولت ذلك. The study dealt with introducing the Rasulid state, through a historical overview of it and a scientific overview, and the study aimed to explain the most important schools of recitation that were established and built by the kings and princes of the Banu Rasul in Yemen to teach the recitation. The methodology of the study was the descriptive approach based on gathering information from various references and sources. The study concluded with a number of results, the most important of which are: that the Rasulid state was one of the largest Sunni countries that was able to extend its influence over most parts of Yemen, and they had a role in the scientific life in Yemen, and they took the most care of the role of science, so they constructed schools, attached them to book coffers, and established schools. Specializing in the teaching of specific sciences such as readings, hadith and jurisprudence. In addition to the joint schools, the establishment of schools was not limited to the sultans of the state, but rather princes, jurists, some ministers and women of the Apostolic House contributed to it, and schools specialized in the science of recitation had a role in producing a large number of reciters at that time. The study also reached a number of recommendations, the most important of which are: expanding the circle of research, seminars and conferences on reading schools in Yemen, printing Yemeni books on the science of readings to introduce the successors to what the predecessors left for them to contribute to motivating them so that they follow their example, and enriching Arab offices with the efforts of Yemenis in building Islamic schools and schools of reading, By printing books and research papers that dealt with that.
Keywords: السياسة التعليمية -- المؤسسات التعليمية -- مدارس الإقراء -- الدولة الرسولية -- اليمن